Glass-based adapter plate heat dissipation structure and preparation method thereof
By using a combination of microcrystalline glass and TGV through-holes on the glass-based adapter plate, the problem of insufficient heat dissipation performance of the existing glass-based adapter plate is solved, and more efficient heat transfer and the reliability of microwave devices are achieved.
Patent Information
- Application Number
- CN202411797999.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-04-25
AI Technical Summary
The existing glass-based adapter plates have insufficient heat dissipation performance, which is difficult to meet the heat dissipation needs of highly integrated microwave devices, which can easily lead to sharp increase in local temperature and cause device failure.
A microcrystalline glass-based adapter plate is used to form latent shadow areas for microcrystalization and TGV through-hole molding through-hole molding through laser pretreatment. Combined with heat treatment and chemical etching, local microcrystalization and TGV through-hole molding are achieved simultaneously to enhance thermal conductivity.
The heat dissipation performance of the glass-based adapter plate is significantly improved, and heat can be transferred efficiently, thereby extending the service life of microwave devices and improving their reliability.
Smart Images

Figure CN119890159A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electronic device packaging, and in particular relates to a glass-based adapter plate heat dissipation structure and a preparation method thereof. Background Art
[0002] The iterative rise of smart terminals, 5G, the Internet of Things and other fields has put forward increasingly stringent requirements for the advanced packaging technology of microelectronic devices. Among them, 2.5D / 3D integration has the characteristics of miniaturization, lightness and flexible design, and has developed rapidly in recent years. As the basis of 2.5D / 3D integration, the adapter board is considered to be an important way to "go beyond Moore's Law" and is expected to become the mainstream technology of advanced packaging.
[0003] Packaging refers to wrapping electronic components such as integrated circuit chips with a shell to protect the chip, facilitate installation, and achieve electrical connections. In the electronics industry, different manufacturers have different chip packaging standards and circuit board interface standards. As an intermediate transition piece, the adapter board can effectively solve this standardization and compatibility problem.
[0004] At present, the adapter board technology mainly includes silicon-based adapter boards based on through silicon vias (TSV) and glass-based adapter boards based on through glass vias (TGV). Among them, silicon-based adapter board technology is more mature, but it has disadvantages such as large dielectric loss and high cost. Glass-based adapter boards are electrically insulating and easier to obtain. Compared with silicon-based adapter boards, glass-based adapter boards have the advantages of excellent dielectric properties and low cost, and are considered to be an effective iterative product of silicon-based adapter boards.
[0005] As packaging technology tends to develop towards miniaturization, and as chip performance improves, its power consumption is also increasing, especially for some high-power chips. If the heat is not dissipated in time, the heat will accumulate inside, causing the device to overheat and cause damage. In the prior art, facing different scenarios, the heat dissipation structure of the glass-based adapter plate is varied, such as dissipating the heat of the chip or device to the surrounding environment through a metal heat dissipation layer. However, no matter which heat dissipation structure is used, the thermal conductivity of the ordinary glass-based adapter plate itself cannot meet the heat dissipation requirements of highly integrated devices.
[0006] At present, when glass-based adapter plates are applied to electronic devices, the heat transfer path is usually electronic devices → glass-based adapter plates → thermal interface materials (TIM) → heat sinks. Due to current technical limitations, the heat dissipation efficiency of this heat transfer path is not high, and it is difficult to meet the heat dissipation requirements of high-power microwave devices. It is easy to cause a sharp increase in local temperature, which in turn causes device failure. The main reasons are as follows:
[0007] (1) Due to the poor thermal conductivity of the glass body, the heat of the ordinary glass-based adapter plate mainly depends on the dense array of copper pillars in the TGV through-holes of the adapter plate. The efficiency of heat transfer from the adapter plate to the thermal interface material is very low;
[0008] (2) Thermal interface materials are usually composed of a matrix and a thermally conductive filler. Since the intrinsic thermal conductivity of the conventional matrix is small and the thermally conductive filler is randomly distributed in the matrix, the heat transfer efficiency inside the thermal interface material is also very low.
[0009] It can be seen that the current glass-based adapter plate is difficult to meet the use requirements of highly integrated microwave devices. Summary of the invention
[0010] In order to solve the technical problems mentioned in the background technology that the glass-based adapter plate heat dissipation structure has poor heat dissipation effect and easily causes microwave device failure, the present invention proposes a glass-based adapter plate heat dissipation structure and a preparation method thereof, which not only meets the excellent dielectric properties of the glass-based adapter plate, but also greatly enhances its heat dissipation performance, thereby improving the service life and reliability of the microwave device.
[0011] The present invention provides a glass-based adapter plate heat dissipation structure, the heat dissipation structure comprising a microcrystalline glass-based adapter plate;
[0012] The microcrystalline glass-based adapter plate includes microcrystalline glass and a plurality of TGV through holes penetrating the upper and lower surfaces of the microcrystalline glass, and the plurality of TGV through holes are arranged at intervals along the thickness direction of the microcrystalline glass.
[0013] In the present invention, the intrinsic thermal conductivity of the microcrystalline glass-based adapter plate is much higher than that of the ordinary glass-based adapter plate. Therefore, after the microcrystalline glass-based adapter plate is adopted in the heat dissipation structure, heat can be efficiently transferred from the adapter plate to the thermal interface material, thereby improving the overall heat dissipation performance of the heat dissipation structure and avoiding failure of the microwave device.
[0014] Preferably, the material of the glass-ceramics is at least one of silicate glass, aluminosilicate glass, aluminate glass or borate glass, preferably aluminosilicate glass;
[0015] Preferably, the thickness of the glass-ceramic is 20-70 μm, the diameter of the TGV through hole is 30-200 μm, and the spacing between adjacent TGV through holes is 100-300 μm.
[0016] In the present invention, when the material of the microcrystalline glass is aluminosilicate glass, its constituent raw materials and their mass percentages include: SiO2 58-70%, Al2O3 14-20%, Na2O 5-10%, CaO 1-5%, MgO 1-5%, ZrO2 1-2%, and TiO2 2-3%.
[0017] Preferably, the heat dissipation structure further comprises a thermal interface material layer and a heat sink;
[0018] The thermal interface material layer is located on an upper and lower surface of the microcrystalline glass-based adapter plate, and the heat sink is located on a surface of the thermal interface material layer away from the microcrystalline glass-based adapter plate.
[0019] Preferably, the thermal interface material layer comprises a matrix material and a thermally conductive filler filled in the matrix material;
[0020] Preferably, the thermally conductive fillers are arranged at intervals along the thickness direction of the thermal interface material layer;
[0021] Preferably, the thickness of the thermal interface material layer is 15-30 μm.
[0022] Compared with the existing thermal interface material layer in which the thermally conductive fillers are randomly distributed in the matrix material, in the present invention, the thermally conductive fillers are controlled to be arranged at intervals along the thickness direction of the thermal interface material layer, so that the heat conducted by the microcrystalline glass-based adapter plate is transferred to the heat sink through a straight path, further improving the heat dissipation performance of the heat dissipation structure.
[0023] Preferably, the matrix material is at least one of silica gel, silicone rubber, silicone rubber, polyurethane, epoxy resin, polyimide or polyester, preferably polyurethane; the thermally conductive filler is at least one of carbon material, metal oxide, metal powder or ceramic material, preferably graphene oxide nanosheets; the radiator is at least one of a copper radiator, a heat pipe radiator, a water-cooled radiator or a composite material radiator, and the thickness is preferably 50-100 μm.
[0024] In the present invention, when the matrix material is polyurethane, its thermal conductivity is 0.03-0.05W / m·K, its elastic modulus is 0.5-3MPa, and its operating temperature is -20-120°C; when the thermal conductive filler is graphene oxide nanosheets, its single layer thickness is 0.3-0.4nm, its stacking thickness is 0.1-5μm, and its lateral size is 1-10μm.
[0025] The present invention also provides a method for preparing the above-mentioned glass-based adapter plate heat dissipation structure, comprising the following steps:
[0026] S1. After laser pretreatment of the glass, a latent image area to be microcrystallized and a latent image area to be formed of a TGV through hole are formed on the glass, wherein the latent image area to be formed of the TGV through hole penetrates the upper and lower surfaces of the glass along the thickness direction of the glass, and the latent image area to be microcrystallized does not penetrate the upper and lower surfaces of the glass along the thickness direction of the glass;
[0027] S2. The glass that has been pre-treated by laser is first heat-treated to form microcrystalline glass in the latent image area to be microcrystallized, and then etched to etch away the glass except the latent image area to be microcrystallized, thereby obtaining a microcrystalline glass-based adapter plate.
[0028] In the present invention, after laser pretreatment of glass, a latent image area to be microcrystallized and to be formed with TGV through holes is formed on the glass, and then heat treatment and chemical etching are performed, so that microcrystallization and TGV through hole formation are achieved simultaneously, thereby obtaining a microcrystalline glass-based adapter plate;
[0029] When TGV through-hole forming is performed directly on microcrystalline glass to produce a microcrystalline glass-based adapter plate, due to the uneven distribution of the microcrystalline phase and the glass phase inside the microcrystalline glass, if through-hole processing is performed directly on the microcrystalline glass, not only will cracking easily occur during the processing, but micropore defects will also be introduced inside the microcrystalline glass. The thermal conductivity of the resulting microcrystalline glass-based adapter plate is far inferior to that of the microcrystalline glass-based adapter plate obtained by the processing method of the present invention.
[0030] Preferably, in step S1, the wavelength of the laser pretreatment is 800-1000nm, the pulse width is 160-280fs, the power is 20-50W, and the scanning speed is 80-120mm / s; in step S2, the heat treatment includes heating treatment first and then cooling treatment; preferably, the temperature of the heating treatment is 600-800℃, the time is 10-30min, and the heating rate is 1-10℃ / min; the temperature of the cooling treatment is 100-150℃, and the cooling rate is 1-10℃ / min.
[0031] In the present invention, a single light source or a dual light source infrared femtosecond laser can be used for laser pretreatment.
[0032] Preferably, the latent image area to be microcrystallized and the latent image area to be formed by the TGV through hole are arranged in a square array with a diameter of 30-200 μm and an adjacent spacing of 100-300 μm, and the lengths of the latent image area to be microcrystallized and the latent image area to be formed by the TGV through hole satisfy the following formula:
[0033]
[0034] The length of the latent image area to be formed by the TGV through hole is L1, which is consistent with the thickness of the glass. The length of the latent image area to be microcrystallized is L2. V1 is the etching rate of the glass in the latent image area, and V2 is the etching rate of the glass in the non-latent image area.
[0035] Preferably, V1 is 0.5-0.8 μm / min, and V2 is 1.8-2.2 μm / min.
[0036] In the present invention, the vertical lengths of the latent image area to be microcrystallized relative to the non-laser processed areas on the upper and lower surfaces of the glass are both (L1-L2) / 2.
[0037] In the present invention, chemical etching has different etching rates for latent image area glass and non-latent image area glass. Therefore, when the vertical length L2 of the latent image area to be microcrystallized and the vertical length L1 of the latent image area to be TGV formed numerically satisfy the above relationship, after chemical etching, all glass except the latent image area to be microcrystallized will be etched away, leaving only the glass in the microcrystallized area, thereby achieving simultaneous microcrystallization and TGV through-hole forming.
[0038] Preferably, the preparation method further comprises the following steps:
[0039] S3. After subjecting one surface of the microcrystalline glass-based adapter plate and the heat sink to plasma activation treatment, the thermal interface material is coated on the surface of the microcrystalline glass-based adapter plate subjected to the plasma activation treatment, and then the surface of the heat sink subjected to the plasma activation treatment is attached thereto, and after sequentially performing electric field treatment and thermal curing treatment, the glass-based adapter plate heat dissipation structure is obtained.
[0040] In the present invention, the thermal interface material is obtained by mixing the matrix and the thermal conductive filler by means of a magnetic stirrer; the thermal interface material can be evenly coated on the surface of the microcrystalline glass by means of a scraper, spin coating, etc.
[0041] Preferably, the mixing temperature is 60-80°C, the mixing time is 25-45 min, and the stirring rate is 800-1200 rpm.
[0042] Preferably, in step S3, the activation medium of the plasma activation treatment is oxygen, the gas pressure is 80-120 Pa, the power is 200-300 W, the treatment time is 60-150 s, the oxygen flow rate is 30-60 sccm, and the working distance is 8-20 mm; the intensity of the electric field treatment is 80-120 V / cm, the time is 25-35 min, and the temperature of the thermal curing treatment is 60-80 ° C, and the time is 22-26 h.
[0043] Beneficial effects of the present invention:
[0044] (1) The microcrystalline glass-based adapter plate of the present invention has the following advantages: high intrinsic thermal conductivity; high mechanical strength and low processing breakage rate; low dielectric loss factor, which is more suitable for high-frequency signal transmission; low thermal expansion coefficient and high dimensional stability; this microcrystalline glass-based adapter plate can significantly improve the thermal conductivity of the overall heat dissipation structure of the microcrystalline glass-based adapter plate.
[0045] (2) The present invention can simultaneously realize local microcrystallization and TGV through-hole forming, which simplifies the process steps and avoids the problem of product cracking caused by performing local microcrystallization and TGV forming in steps; further, the microcrystallization area can be flexibly selected based on the overall structural design (such as the distribution area of the filler in the TIM).
[0046] (3) The present invention uses an external electric field to orient the thermal conductive filler in the matrix, thereby achieving linear heat transfer and significantly improving the overall thermal conductivity of the microcrystalline glass-based adapter plate heat dissipation structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 It is a schematic structural diagram of a latent image area to be formed with a TGV through hole and a latent image area to be microcrystallized on glass in Example 1 of the present invention;
[0048] Figure 2 Schematic diagram of the structure of the glass-ceramic-based adapter plate in Example 1 of the present invention;
[0049] Figure 3 It is a structural schematic diagram of the heat dissipation structure of the glass-based adapter plate described in Example 1 of the present invention. DETAILED DESCRIPTION
[0050] Example 1
[0051] This embodiment provides a glass-based adapter plate heat dissipation structure, and the preparation method thereof includes:
[0052] S1. A single-source infrared femtosecond laser with a laser wavelength of 850nm, a pulse width of 180fs, a power of 25W, a scanning speed of 100mm / s, and a focal depth of 40μm is used to perform laser pretreatment on a target area of aluminosilicate glass with a thickness of 40μm (the raw materials and their mass percentages include: SiO265%, Al2O318%, Na2O 7%, CaO3%, MgO 3%, ZrO21.5%, TiO22.5%) to form a latent image area to be formed with a depth of 40μm, a diameter of 50μm, and a mutual spacing of 120μm; then the focal depth is adjusted to 30μm, and the remaining area of the glass is laser pretreated to form a latent image area to be microcrystallized with a depth of 30μm. The latent image area to be microcrystallized has a thickness of 5μm and is not laser pretreated. The specific structure is shown in the figure below. Figure 1 As shown;
[0053] S2. The glass pretreated by laser is first heated to 650°C at a rate of 10°C / min, kept warm for 15 minutes, then cooled to 120°C at a rate of 10°C / min, and then naturally cooled to room temperature. At this time, the glass in the latent image area to be formed by the TGV through hole and the latent image area to be microcrystallized forms microcrystalline glass; the glass is then immersed in an acid solution (the acid solution is a mixture of 40% HF, 70% HNO3 and 98% H2SO4 in a volume ratio of 1:1:1) for chemical corrosion, and the etching rate of the glass without laser pretreatment is controlled to be 0.5μm / min, and the etching rate of the microcrystalline glass is controlled to be 2.0μm / min. After etching for 10 minutes, a microcrystalline glass-based adapter plate with a thickness of 30μm, a TGV through hole depth of 30μm, a diameter of 50μm, and a center distance between adjacent TGV through holes of 120μm is formed. The specific structure is shown in the figure below Figure 2 As shown;
[0054] S3, polyurethane (thermal conductivity of 0.05w / m·K, elastic modulus of 1.5MPa, use temperature of -20-120°C) and 0.5wt% of polyurethane mass of graphene oxide nanosheets (single layer thickness of 0.4nm, stacking thickness of 2μm, lateral size of 5μm) were mixed, and the mixture was evenly mixed after magnetic stirring for 30min, the mixing temperature was 65°C, and the stirring speed was 1000rpm to obtain a thermal interface material;
[0055] S4. Oxygen is used as the activation medium, and the gas pressure is adjusted to 100 Pa, the power is 220 W, the processing time is 90 s, the oxygen flow rate is 50 sccm, and the working distance is 13 mm. After the surfaces of the microcrystalline glass-based adapter plate and the copper heat sink (thickness is 60 μm, thermal conductivity is 390 w / m·K) are plasma activated, a thermal interface material with a thickness of 20 μm is evenly coated on the surface of the microcrystalline glass-based adapter plate after the plasma activation treatment by a scraper, and then the surface of the copper heat sink after the plasma activation treatment is attached, and then placed under a vertical DC electric field with an intensity of 100 V / cm for 30 minutes, and then cured at 60°C for 24 hours, the heat dissipation structure of the glass-based adapter plate is obtained. The specific structure is shown in the figure below. Figure 3 shown.
[0056] The above-mentioned glass-based adapter plate heat dissipation structure proposed in this embodiment substantially comprises: a microcrystalline glass-based adapter plate, a thermal interface material layer and a copper heat sink; the thermal interface material layer is located on an upper and lower surface of the microcrystalline glass-based adapter plate, and the copper heat sink is located on a surface of the thermal interface material layer away from the microcrystalline glass-based adapter plate;
[0057] Among them, the microcrystalline glass-based adapter plate includes microcrystalline glass with a thickness of 30μm and multiple TGV through holes running through the upper and lower surfaces of the microcrystalline glass. The diameter of the TGV through hole is 50μm, the depth of the TGV through hole is 30μm, and the center spacing between adjacent TGV through holes is 120μm; the thermal interface material layer is composed of a polyurethane matrix and graphene oxide fillers arranged at intervals along the thickness direction of the thermal interface material layer.
[0058] Reference Figure 1 As shown, after the glass described in this embodiment is pre-treated by laser, a latent image area dM12 to be formed with a TGV through hole and a latent image area dM11 to be microcrystallized are formed on the glass substrate dM1.
[0059] Reference Figure 2 As shown, the microcrystalline glass-based adapter plate described in this embodiment is recorded as structure M1, which is composed of a microcrystalline glass substrate M11 and a plurality of TGV through holes M12 penetrating the upper and lower surfaces of the microcrystalline glass substrate M11.
[0060] Reference Figure 3 As shown, the glass-based adapter plate heat dissipation structure described in this embodiment is composed of three structures: a microcrystalline glass-based adapter plate M1, a thermal interface material layer M2 and a copper heat sink M3; wherein the thermal interface material layer M2 is composed of a polyurethane matrix M21 and a graphene oxide filler M22 arranged perpendicular to the thermal interface material layer.
[0061] Example 2
[0062] This embodiment provides a glass-based adapter plate heat dissipation structure, and its preparation method is the same as that of embodiment 1, except that in step S1, a single-light-source infrared femtosecond laser with a laser wavelength of 900nm, a pulse width of 200fs, a power of 25W, a scanning speed of 100mm / s, and a focal depth of 60μm is used to perform laser pretreatment on a target area of aluminosilicate glass with a thickness of 60μm, so as to form a latent image area to be formed with a depth of 60μm, a diameter of 80μm, and a mutual spacing of 150μm; then the focal depth is adjusted to 45μm, and the remaining area of the glass is laser pretreated to form a latent image area to be microcrystallized with a depth of 45μm, and non-laser pretreated glass with a thickness of 7.5μm is left on the upper and lower surfaces of the latent image area to be microcrystallized respectively;
[0063] In step S2, etching is performed for 15 minutes to form a microcrystalline glass-based adapter plate with a thickness of 45 μm, a TGV through-hole depth of 45 μm, a diameter of 80 μm, and a center spacing of adjacent TGV through-holes of 150 μm; in step S3, the lateral connection size of the graphene oxide nanosheet is 45 μm.
[0064] Example 3
[0065] This embodiment provides a glass-based adapter plate heat dissipation structure, and its preparation method is the same as that of embodiment 1, except that in step S1, a single-light-source infrared femtosecond laser with a laser wavelength of 950nm, a pulse width of 220fs, a power of 35W, a scanning speed of 100mm / s, and a focal depth of 80μm is used to perform laser pretreatment on a target area of aluminosilicate glass with a thickness of 80μm, so as to form a latent image area to be formed with a depth of 80μm, a diameter of 100μm, and a mutual spacing of 180μm; then the focal depth is adjusted to 80μm, and the remaining area of the glass is laser pretreated to form a latent image area to be microcrystallized with a depth of 60μm, and non-laser pretreated glass with a thickness of 10μm is respectively left on the upper and lower surfaces of the latent image area to be microcrystallized;
[0066] In step S2, etching is performed for 20 minutes to form a microcrystalline glass-based adapter plate with a thickness of 60 μm, a TGV through-hole depth of 60 μm, a diameter of 100 μm, and a center spacing of adjacent TGV through-holes of 180 μm; in step S3, the lateral connection size of the graphene oxide nanosheet is 45 μm.
[0067] Comparative Example 1
[0068] This comparative example proposes a glass-based adapter plate heat dissipation structure, and its preparation method is the same as that of Example 1, except that the operation of "placing it under a vertical DC electric field with an intensity of 100 V / cm for 30 minutes" is omitted in step S4.
[0069] Comparative Example 2
[0070] This comparative example proposes a glass-based adapter plate heat dissipation structure, and its preparation method is the same as that of Example 1, except that in step S1, the operation of "adjusting the focal depth to 30μm, performing laser pretreatment on the remaining area of the glass to form a latent image area to be microcrystallized with a depth of 30μm, and leaving un-laser pretreated glass with a thickness of 5μm on the upper and lower surfaces of the glass in the latent image area to be microcrystallized" is omitted.
[0071] Comparative Example 3
[0072] This comparative example proposes a glass-based adapter plate heat dissipation structure, and its preparation method is the same as that of Example 1, except that in step S1, a single-light-source infrared femtosecond laser with a laser wavelength of 850nm, a pulse width of 180fs, a power of 25W, a scanning speed of 100mm / s, and a focal depth of 30μm is used to perform laser pretreatment on aluminosilicate glass with a thickness of 30μm (the raw materials and their mass percentages include: SiO265%, Al2O318%, Na2O7%, CaO 3%, MgO 3%, ZrO21.5%, TiO22.5%), and a fully microcrystalline latent image with a depth of 30μm is formed on the glass;
[0073] In step S2, the glass after laser pretreatment is first heated to 650°C at a rate of 10°C / min, kept warm for 15 minutes, then cooled to 120°C at a rate of 10°C / min, and then naturally cooled to room temperature. At this time, the glass forms microcrystalline glass; then, a laser etching process (using a single-light source infrared femtosecond laser with a laser wavelength of 1050nm, a power of 30W, a scanning speed of 50mm / s, and a repetition frequency of 200kHz) is used to form TGV through holes with a depth of 30μm, a diameter of 50μm, and a center spacing of 120μm between adjacent TGV through holes.
[0074] Comparative Example 4
[0075] This comparative example proposes a glass-based adapter plate heat dissipation structure, and its preparation method is the same as that of Example 1, except that in step S1, the operation of "adjusting the focal depth to 30 μm, laser pre-treating the remaining area of the glass to form a latent image area to be microcrystallized with a depth of 30 μm, and leaving un-laser pre-treated glass with a thickness of 5 μm on the upper and lower surfaces of the glass in the latent image area to be microcrystallized" is omitted;
[0076] In step S2, the glass after laser pretreatment is first heated to 650°C at a rate of 10°C / min, kept at this temperature for 15 minutes, then cooled to 120°C at a rate of 10°C / min, and then naturally cooled to room temperature. At this time, the glass in the latent shadow area of the TGV through hole forming forms a microcrystalline glass; the glass is then immersed in an acid solution for chemical etching, and the etching rate of the glass without laser pretreatment is controlled to be 0.5μm / min, and the etching rate of the microcrystalline glass is controlled to be 2.0μm / min. After etching for 10 minutes, a TGV through hole with a thickness of 30μm and a depth of 30μm and a diameter of 50 is formed. μm, and the center spacing between adjacent TGV through holes is 120 μm; the ordinary glass-based adapter plate is laser pretreated with a single-light source infrared femtosecond laser with a laser wavelength of 850nm, a pulse width of 180fs, a power of 25W, a scanning speed of 100mm / s, and a focal depth of 30μm, and then the laser-pretreated glass is first heated to 650℃ at a rate of 10℃ / min, kept warm for 15min, and then cooled to 120℃ at a rate of 10℃ / min, and then naturally cooled to room temperature. At this time, the ordinary glass-based adapter plate forms a microcrystalline glass-based adapter plate.
[0077] The performance of the heat dissipation structure of the glass-based adapter plate obtained in the above examples and comparative examples is shown in Table 1 below:
[0078] Table 1 Performance test results of the glass-based adapter plate heat dissipation structure of the embodiment and the comparative example
[0079]
[0080] As can be seen from Table 1 above, in Comparative Example 1, since the thermal interface material is not treated in a DC electric field after coating, the thermal conductive filler is distributed in a disorderly manner in the matrix material, and the heat cannot be transferred from the thermal interface material layer to the heat sink in a straight line path, so the thermal conductivity of the glass-based adapter plate heat dissipation structure is very low. In Comparative Example 2, since laser pretreatment is not used to form the area to be microcrystallized in the aluminosilicate glass, the adapter plate in the obtained heat dissipation structure is an ordinary glass-based adapter plate rather than a microcrystalline glass-based adapter plate, so the heat dissipation thermal conductivity is low, and heat cannot be effectively transferred from the glass-based adapter plate to the thermal interface material. In Comparative Example 3, since local microcrystallization and TGV forming are not performed simultaneously, but a TGV through-hole array is directly formed in the aluminosilicate microcrystalline glass by laser etching, although a microcrystalline glass-based adapter plate is obtained, due to the introduction of microcracks, micropores and other defects in the microcrystalline glass when the TGV through-holes are laser-etched, the thermal conductivity of the glass adapter plate heat dissipation structure is still low. In Comparative Example 4, since local microcrystallization and TGV forming are not carried out simultaneously, local microcrystallization is carried out in the glass substrate with a TGV through-hole structure formed therein through laser pretreatment and heat treatment. Although a microcrystalline glass-based adapter plate is finally obtained, the thermal conductivity of the heat dissipation structure of the glass adapter plate is still low. Moreover, since local microcrystallization and TGV forming are not carried out simultaneously, the product is prone to cracking.
[0081] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A glass-based adapter plate heat dissipation structure, characterized in that: The heat dissipation structure includes a glass-ceramic-based adapter plate; The microcrystalline glass-based adapter plate includes microcrystalline glass and a plurality of TGV through holes penetrating the upper and lower surfaces of the microcrystalline glass, and the plurality of TGV through holes are arranged at intervals along the thickness direction of the microcrystalline glass.
2. The glass-based adapter plate heat dissipation structure according to claim 1, characterized in that: The material of the glass-ceramics is at least one of silicate glass, aluminosilicate glass, aluminate glass or borate glass, preferably aluminosilicate glass; Preferably, the thickness of the glass-ceramic is 20-70 μm, the diameter of the TGV through hole is 30-200 μm, and the spacing between adjacent TGV through holes is 100-300 μm.
3. The glass-based adapter plate heat dissipation structure according to claim 1 or 2, characterized in that: The heat dissipation structure also includes a thermal interface material layer and a heat sink; The thermal interface material layer is located on an upper and lower surface of the microcrystalline glass-based adapter plate, and the heat sink is located on a surface of the thermal interface material layer away from the microcrystalline glass-based adapter plate.
4. The glass-based adapter plate heat dissipation structure according to claim 3, characterized in that: The thermal interface material layer includes a matrix material and a thermally conductive filler filled in the matrix material; Preferably, the thermally conductive fillers are arranged at intervals along the thickness direction of the thermal interface material layer; Preferably, the thickness of the thermal interface material layer is 15-30 μm.
5. The glass-based adapter plate heat dissipation structure according to claim 4, characterized in that: The matrix material is at least one of silica gel, silicone rubber, silicone rubber, polyurethane, epoxy resin, polyimide or polyester, preferably polyurethane; the thermal conductive filler is at least one of carbon material, metal oxide, metal powder or ceramic material, preferably graphene oxide nanosheets; the radiator is at least one of a copper radiator, a heat pipe radiator, a water-cooled radiator or a composite material radiator, and the thickness is preferably 50-100 μm.
6. A method for preparing the glass-based adapter plate heat dissipation structure according to any one of claims 1 to 5, characterized in that: The steps include: S1. After laser pretreatment of the glass, a latent image area to be microcrystallized and a latent image area to be formed of a TGV through hole are formed on the glass, wherein the latent image area to be formed of the TGV through hole penetrates the upper and lower surfaces of the glass along the thickness direction of the glass, and the latent image area to be microcrystallized does not penetrate the upper and lower surfaces of the glass along the thickness direction of the glass; S2. The glass that has been pre-treated by laser is first heat-treated to form microcrystalline glass in the latent image area to be microcrystallized, and then etched to etch away the glass except the latent image area to be microcrystallized, thereby obtaining a microcrystalline glass-based adapter plate.
7. The method for preparing the glass-based adapter plate heat dissipation structure according to claim 6, characterized in that: In step S1, the wavelength of the laser pretreatment is 800-1000nm, the pulse width is 160-280fs, the power is 20-50W, and the scanning speed is 80-120mm / s; In step S2, the heat treatment includes heating treatment first and then cooling treatment; preferably, the temperature of the heating treatment is 600-800°C, the time is 10-30min, and the heating rate is 1-10°C / min; the temperature of the cooling treatment is 100-150°C, and the cooling rate is 1-10°C / min.
8. The method for preparing the glass-based adapter plate heat dissipation structure according to claim 6 or 7, characterized in that: The latent image area to be microcrystallized and the latent image area to be formed by the TGV through hole are arranged in a square array with a diameter of 30-200 μm and an adjacent spacing of 100-300 μm, and the lengths of the latent image area to be microcrystallized and the latent image area to be formed by the TGV through hole satisfy the following formula: The length of the latent image area to be formed with TGV through holes is L1, the length of the latent image area to be microcrystallized is L2, V1 is the etching rate of the glass in the latent image area, and V2 is the etching rate of the glass in the non-latent image area; Preferably, V1 is 0.5-0.8 μm / min, and V2 is 1.8-2.2 μm / min.
9. The method for preparing the glass-based adapter plate heat dissipation structure according to any one of claims 6 to 8, characterized in that: The following steps are also included: S3. After subjecting one surface of the microcrystalline glass-based adapter plate and the heat sink to plasma activation treatment, the thermal interface material is coated on the surface of the microcrystalline glass-based adapter plate subjected to the plasma activation treatment, and then the surface of the heat sink subjected to the plasma activation treatment is attached thereto, and after sequentially performing electric field treatment and thermal curing treatment, the glass-based adapter plate heat dissipation structure is obtained.
10. The method for preparing the glass-based adapter plate heat dissipation structure according to claim 9, characterized in that: In step S3, the activation medium of the plasma activation treatment is oxygen, the gas pressure is 80-120Pa, the power is 200-300W, the treatment time is 60-150s, the oxygen flow rate is 30-60sccm, and the working distance is 8-20mm; the intensity of the electric field treatment is 80-120V / cm, the time is 25-35min, and the temperature of the thermal curing treatment is 60-80°C, and the time is 22-26h.
Citation Information
Cited By
Heat dissipation structure for glass-based interposer, and manufacturing method therefor
WO2026124268A1